2018
DOI: 10.1017/s1351324918000190
|View full text |Cite
|
Sign up to set email alerts
|

Weighting-based semantic similarity measure based on topological parameters in semantic taxonomy

Abstract: Semantic measures are used in handling different issues in several research areas, such as artificial intelligence, natural language processing, knowledge engineering, bioinformatics, and information retrieval. Hierarchical feature-based semantic measures have been proposed to estimate the semantic similarity between two concepts/words depending on the features extracted from a semantic taxonomy (hierarchy) of a given lexical source. The central issue in these measures is the constant weighting assumption that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Finally, in comparison with the weight-based method proposed by Saif et al [38], our model combined with Li or Liu-1 is equal to or exceeds it on MC30, surpass it on the RG65 and SimLex666 datasets, but defeat it on AG203. Overall, our model is slightly superior to Saif's method in terms of measurement accuracy.…”
Section: Discussion a Discussion On Wordnet Edge Weight Modelmentioning
confidence: 78%
See 2 more Smart Citations
“…Finally, in comparison with the weight-based method proposed by Saif et al [38], our model combined with Li or Liu-1 is equal to or exceeds it on MC30, surpass it on the RG65 and SimLex666 datasets, but defeat it on AG203. Overall, our model is slightly superior to Saif's method in terms of measurement accuracy.…”
Section: Discussion a Discussion On Wordnet Edge Weight Modelmentioning
confidence: 78%
“…Saif et al [38] considered the semantic representation of a concept as a set of concepts that are extracted from its hypernym-concepts in a semantic taxonomy, and they then proposed four weight mechanisms to weigh the degree of relevance of features by using topological parameters (edge, depth, descendants, and density) in a semantic taxonomy. The weight mechanism with descendants has achieved the best results in their experiments, so we just show this one.…”
Section: ) Weighting-based Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Weighted Kernel Density Estimation (WKDE) [43,44] based on point weights has proved effective. For the semantic similarity measuring task, constant weighting assumption-based semantic similarity [45] measure between two concepts/words holds better performance for the semantic representation of the concept/words but holds the same weighting relevance. Later, it found that the weight propagation mechanism [46,47] for augmenting input with semantic information achieves desired performance and removes the same weighting curse for concepts/words.…”
Section: Literature Reviewmentioning
confidence: 99%